Empiryczna analiza porównawcza dokładności wybranych metod prognozowania w warunkach braku pełnej informacji - Markiewicz, Alicja; Zawadzki, Jan (Empirical Comparative Analysis of Accuracy of Selected Forecasting Method in Situation of Lack of Full Information, 2006)
The article presents results of missing data forecasting in economical time series with seasonal fluctuations. Accuracy of inter- and extrapolation forecasts was compared by using predictors based on time series models with trigonometrical polynomial, hierarchical and neural networks. The variables with different intensity of seasonality were used as samples.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 92-102